2017
DOI: 10.1155/2017/9460958
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Superficial Femoral Arteriovenous Fistula and Severe Venous Stasis Ulceration, Managed with an Iliac Extender Prosthesis

Abstract: Most femoral artery arteriovenous fistulas occur as a result of percutaneous interventions. However, arteriovenous fistulas can occur in the setting of trauma, with resultant consequences such as heart failure, steal syndrome, or venous insufficiency. Indications for endovascular repair in this setting are limited to patients who are at too high risk for anesthesia, have a hostile groin, or would not survive significant bleeding. We report the case of a traumatic femoral arteriovenous fistula, causing severe v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…There are no clear guidelines as to what the next diagnostic step is. Although angiography remains the gold standard, it is common among practitioners to do a CTA as a second step (Table 1 ) [ 16 , 25 ]. In a systematic review and meta-analysis by Jens et al, CTA was shown to have a sensitivity and specificity of 96.2 and 99.2% respectively [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are no clear guidelines as to what the next diagnostic step is. Although angiography remains the gold standard, it is common among practitioners to do a CTA as a second step (Table 1 ) [ 16 , 25 ]. In a systematic review and meta-analysis by Jens et al, CTA was shown to have a sensitivity and specificity of 96.2 and 99.2% respectively [ 26 ].…”
Section: Discussionmentioning
confidence: 99%